Validation of the Serbian version of the Asthma Control Test - Milenković, Branislava; Ristić, Snežana; Mirović, Danijela; Dimić Janjić, Sanja; Janković, Jelena; Djurdjević, Nataša; Davičević-Elez, Žaklina; Lukić, Tamara (Vojnosanitetski pregled, 2021)
Background/Aim. Asthma still remains poorly controlled in the majority of patients. The Asthma Control Test (ACT) is a short and useful patient-administered questionnaire for identification of patients with poor asthma control in clinical settings. The aim of this study was to validate a Serbian version of the ACT in the adults with asthma. Methods. A total of 250 consecutive adult asthmatic patients were recruited in a prospective observational study. The exclusion criteria were chronic respiratory disease and acute respiratory tract infection in preceding 4 weeks. Results. The spirometry and ACT questionnaire were performed on the baseline visit and 6 months later. The ACT test was completed by 98.8% of patients with the mean time of completion of 4.5 minutes. The correlation of ACT score and lung function parameters (forced expiratory volume in 1 second – FEV1 and forced vital capacity – FVC) was significant (p = 0.016 and p = 0.002, respectively). A change in the ACT scores between baseline and 6-months visit was not associated with a change in FVC and FEV1. The ACT score had excellent diagnostic accuracy according to the physicians asthma control classification and even outstanding accuracy according to the patients’ classification. Conclusion. The results of this study confirm the reliability, validity and accuracy of Serbian version of the ACT, contributing to established value of original ACT test and with consistent findings as the previously reported validity of ACT in other languages. Therefore, it should be utilized more in everyday clinical practice as a useful and reliable tool of asthma control assessment.
Keywords: asthma; surveys and questionnaires; serbia